2012
DOI: 10.1016/j.virol.2011.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 E6 and E 7 proteins alter NF-kB in cultured cervical epithelial cells and inhibition of NF-kB promotes cell growth and immortalization

Abstract: The NF-kB family of transcription factors regulates important biological functions including cell growth, survival and the immune response. We found that Human Papillomavirus type 16 (HPV-16) E7 and E6/E7 proteins inhibited basal and TNF-alpha-inducible NF-kB activity in human epithelial cells cultured from the cervical transformation zone, the anatomic region where most cervical cancers develop. In contrast, HPV-16 E6 regulated NF-kB in a cell type- and cell growth-dependent manner. NF-kB influenced immortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 48 publications
5
80
0
2
Order By: Relevance
“…HPV E6 and E7 proteins inhibit NF-B activity in cervical epithelial cells and downregulate expression of the interferon-responsive genes (27,28). Furthermore, HPV-16 E6 binds and inactivates IRF3, a major mediator of the interferon response; inhibits Toll-like receptor 9 activity (29); and interferes with PKR activation (30).…”
Section: G3bp1 and G3bp1-induced Sgs Restrict Enterovirus Infectionmentioning
confidence: 99%
“…HPV E6 and E7 proteins inhibit NF-B activity in cervical epithelial cells and downregulate expression of the interferon-responsive genes (27,28). Furthermore, HPV-16 E6 binds and inactivates IRF3, a major mediator of the interferon response; inhibits Toll-like receptor 9 activity (29); and interferes with PKR activation (30).…”
Section: G3bp1 and G3bp1-induced Sgs Restrict Enterovirus Infectionmentioning
confidence: 99%
“…E7 can suppress the activity of several key cellular tumor suppressors, such as pRb (34), NF-B (35,36), and p300 (37). An examination of the promoter of miR-145 revealed that p65 (Rel A), part of the NF-B transcriptional machinery, has two binding regions.…”
mentioning
confidence: 99%
“…An examination of the promoter of miR-145 revealed that p65 (Rel A), part of the NF-B transcriptional machinery, has two binding regions. E7 reduces NF-B activity in HPV-positive cells (35,36), and this may contribute to repression of miR-145 expression.…”
mentioning
confidence: 99%
“…Initially, E6 and E7 oncogenes suppress NF-kappaB in order to avoid the innate immune response and achieve the persistent infection. By establishing the persistence and chronic inflammation, they increase the activity of NF-kappaB signaling pathway that contributes to the development of cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%